Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Lokasi Terhadap Kepuasan Pelanggan Di Hotel Alana Sentul - Lukman Nul Hakim; Salman Paludi (LPPM Universitas Asa Indonesia, 2023)
The essence of this research is to find out how the influence of service quality, price perception, and location at the Alana Sentul Hotel has on customer satisfaction. This study used the purposive sampling method to select 100 respondents as participants. Data collection was carried out through the use of questionnaires and then tested for validity and reliability. Multiple linear analysis using SPSS 24 for Windows software was used to analyze the data. The F-test is used to evaluate the overall hypothesis, while the T-test is used to investigate the impact of each subsection. The findings show that Price Perception has no effect on Customer Satisfaction, Service Quality has an effect on Customer Satisfaction. Location also plays a big role and influences a lot. At the Alana Sentul Hotel, Location and Service Quality are Important Factors for Customer Satisfaction. However, Perceived Price has no significant effect on Customer Satisfaction at the Alana Sentul Hotel.